PEMANFAATAN TEKNOLOGI TEPAT GUNA BERBASIS STRATEGI DIVERSIFIKASI KONSENTRIS UNTUK MENINGKATKAN KUALITAS USAHA PRODUKSI MINYAK CENGKEH - Muhammad Hasan; Sitti Rapika; M. Ihsan Said Ahmad; Tuti Supatminingsih; Mustari Mustari (Jurnal Kewirausahaan dan Bisnis, 2021)
A business strategy is a very important aspect of running a business so that the business is able to develop and compete competitively with its competitors, thus impacting on sales and operating revenues. This study aims to assess the use of appropriate technology based on a concentric diversification strategy to improve the quality of clove oil production in Batu Putih Village, Tellu Limpoe District, Bone Regency. This type of study is descriptive qualitative with 3 informants. Data collection techniques by means of observation, interviews, and documentation. The technique of validating the data used source triangulation. The results of this study indicate that the quality of business in clove oil production uses a quality control system through the PDCA cycle, namely planning, working or processing, checking or evaluation and corrective action. In planning, the business owner makes careful considerations in accordance with the applicable operational standards so that the quality of the clove oil to be made meets the criteria and is suitable for sale. In the aspect of doing, clove oil business owners learn by taking part in trainings conducted by related agencies to get maximum results. In addition, reading articles about clove oil manufacturing innovations is also important because it is necessary to upgrade the latest knowledge about clove oil processing. In the checking aspect, entrepreneurs set limits in determining criteria when making clove oil so that the quality of the product made is feasible to be marketed because clove oil is a product that is sought after by consumers. In the aspect of action, the business owner has rearranged the procedure for making clove oil which has undergone improvements due to improvements mainly in working time efficiency of the clove oil business unit. The results of the product quality analysis improved the quality of the clove oil business in Batu Putih Village, Tellu Limpoe District, Bone Regency.Key words: Appropriate Technology, Business Quality, Clove Oil, Concentric Diversification Strategy